2009
DOI: 10.14723/tmrsj.34.501
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Heavy-Metal-Anion Utilizing <i>N,N</i>-Dimethylaminopropylacrylamide/Acrylamide Gels

Abstract: In the present study, in order to examine the N,N-dimethylaminopropylacrylamide/acrylamide {DMAPAA/AAm} hydrogels' capabilities of repetitive heavy-metal-anion recovery from waste fluid, the authors performed successive Cr(VI) adsorption and the adsorbed-Cr(VI) desorption experiments. It has been proved that the DMAPAA/AAm gels show both of the high Cr(VI)-capturing functionality and Cr(VI)-desorption efficiencies. The results in the present study have demonstrated a possibility of a heavy-metal-anion recyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 4 publications
1
35
0
Order By: Relevance
“…As mentioned in the introduction, the authors have been investigating the heavy-metal adsorption and desorption properties of hydrogels [5][6][7][8][9] in order to create new environment purifying materials and to devise new processes which can resolve the current social problems on both the landfillsite-depletion and the heavy-metal-resource drain. The authors have considered that ideal heavy-metal recovery materials should be also recyclable themselves from the viewpoint of the resource saving and reduction of waste generation, which requires the regeneration of the adsorbent after use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned in the introduction, the authors have been investigating the heavy-metal adsorption and desorption properties of hydrogels [5][6][7][8][9] in order to create new environment purifying materials and to devise new processes which can resolve the current social problems on both the landfillsite-depletion and the heavy-metal-resource drain. The authors have considered that ideal heavy-metal recovery materials should be also recyclable themselves from the viewpoint of the resource saving and reduction of waste generation, which requires the regeneration of the adsorbent after use.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have observed high heavy-metal-ion capturing efficiencies of some ionized-hydrogels in the previous studies [5][6][7][8][9]: for example, the heavy-metal cation-capturing efficiency of poly(acrylamide/sodium acrylate) (PAAm/SA) gel is estimated ~20wt% of network polymer [5]. The hydrogel which adsorbs heavy-metal cation can be also made with a biodegradable material such as sodium carboxymethylcellulose (CMC-Na) by irradiating γ-ray instead of usually used toxic cross-linker; its heavy-metal-cation capturing efficiency is comparable to the PAAm/SA gel [5].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the authors' previous studies, measured were the heavy metal capturing efficiencies both of the positively [9,10,17,18,21] and negatively [11][12][13][14][15][16][19][20][21] ionized hydrogels: The heavy-metal cation capturing efficiency of sodium acrylate/acrylamide (SA/AAm) and carboxymethylcellulose (CMC-Na) gels were found to be ~20 wt% of network polymer [9] [10,21]. As for the heavy-metal-anion capturing hydrogels [11][12][13][14][15][16][19][20][21], their capturing efficiencies are larger than those of SA/AAm and CMC-Na gels, which are much larger than those of zeolites and ion-exchange resins.…”
Section: Introductionmentioning
confidence: 99%